Perception of safety and physical activity in adults: a systematic review - Eduardo Caputo; Airton Rombaldi; Tanísia Medeiros; Marcelo Silva (Revista Brasileira de Atividade Física e Saúde)
The process of urbanization observed in recent decades has brought with it some consequences for the quality of life and change in the profile of diseases, which are related to higher rates of physical inactivity. The lack of sufficient physical activity (PA) is currently being considered as a risk factor for diseases and comorbidities, especially in adult populations. Thus, the aim of the present study was to systematically review the scientific findings in the literature on the practice of physical activity among adults and its relation to the perception of security in urban centers, published between 2005 and 2014. The search process was conducted using the PubMed, MedLine and LILACS databases, and the reference lists of selected articles used the following key words: "physical activity", "violence" and "safety". Initially, 303 articles related to the subject under study were found. However, after analyses and the establishment of inclusion criteria, 13 articles were included in this review. It was concluded that the reduction in crime and improvement in traffic and in the environment for walking are key factors to perceive safety in a district. Despite the evidence showing that traffic safety, adequate lighting and improvements in the aesthetics of districts contribute to the perception of safety, the results are yet inconclusive.